1990
DOI: 10.1002/eji.1830200509
|View full text |Cite
|
Sign up to set email alerts
|

Antigen‐induced inhibition of autoimmune response to rat male accessory glands: distinct role of I‐A and I‐E‐positive peritoneal cells

Abstract: The present report describes the structural and functional characteristics of the population of peritoneal cells (PC) from rats injected intraperitoneally (i.p.) 2 h or 24 h previously with a suppressor dose of a purified fraction (FI) of rat male accessory glands (RAG: FI-PC2h and FI-PC24h, respectively). Both populations of PC showed the presence of the autoantigens of RAG on their membrane. The study of cell surface marker showed increase of OX17 (I-E) in FI-PC2h and OX6 (I-A) in FI-PC24h. I.p. injection of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1991
1991
1996
1996

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Using another experimental model of autoimmunity against rat male sex accessory glands induced by immunization with a chemically modified accessory gland saline extract (MRAG) in complete Freund's adjuvant (CFA), we have previously shown that a purified fraction of rat male accessory glands intraperitoneally administered in low doses and soluble form prevents the cellular and humoral autoimmune response when animals are subsequently challenged with MRAG in CFA (Ferro et al , 1985(Ferro et al , , 1990Rivero et al, 199 1). Application of a similar experimental model to EAE demonstrated inhibition of the clinical signs of the disease with a concurrent suppression of the proliferative response of mononuclear cells to MBP (Rivero et al, 1995(Rivero et al, , 1996.…”
Section: Introductionmentioning
confidence: 99%
“…Using another experimental model of autoimmunity against rat male sex accessory glands induced by immunization with a chemically modified accessory gland saline extract (MRAG) in complete Freund's adjuvant (CFA), we have previously shown that a purified fraction of rat male accessory glands intraperitoneally administered in low doses and soluble form prevents the cellular and humoral autoimmune response when animals are subsequently challenged with MRAG in CFA (Ferro et al , 1985(Ferro et al , , 1990Rivero et al, 199 1). Application of a similar experimental model to EAE demonstrated inhibition of the clinical signs of the disease with a concurrent suppression of the proliferative response of mononuclear cells to MBP (Rivero et al, 1995(Rivero et al, , 1996.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the inhibition was antigen specific because the RAG FI-pretreated animals could effectively mount an immune response to Tuxoplasma gondii antigens [20]. The cell types involved in the suppression included MRAG-specific, cyclophosphamide CY-sensitive, inducer-phase Ts cells, CYand irradiation-sensitive, effector-phase suppressor cells and I-E+ APC [7,21]. The results presented here show clearly that it is more difficult to induce suppression to autoantigen of RAG in old rats.…”
Section: Discussionmentioning
confidence: 65%
“…Taken together, these findings support our previous results on the role of I-E+ PC in the induction of suppression in RAG autoimmunity. In fact, it was previously demonstrated [7] that I-E+ PC from rats injected i.p. with FI of RAG,but not with an unrelated antigen,were involved in the induction of MRAG-specific inducer-phase T, cells and that I-A+ PC from FI of RAG-pretreated rats were involved in the induction of cells responsible for the autoimmune response.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation